Shrek: do conto aos filmes, em uma sucessão de paródias - Souza, Denise Loreto de [UNESP] (2013)
We have seen from the last two decades of the 20th century, the rereading of the fairy tale genre both in literature aimed at children in cinema in general, and in the animated film in particular. I realize that the parodic procedure is present in the rereading process, being contemplated, in that gesture, some aspects of traditional fairy tales and lefting intacts other elements. It is from the question of how these narratives work to rereading of fairy tales that I begin the investigation that motivates this research project: how the narrative Shrek!, by William Steig, and its film adaptations, by Dreamworks Animation studios, proceed the genre rereading. The research will include, first, the study of the fairy tale genre, its structure and semantic aspects, from reading the narrative of Steig, to, then, investigate the textual dialogue between the work and the genre it belongs. Later, the story made into a film will be the subject of research to investigate how the fairy tale genre is rereaded by the cinema support from the ingredients provided by the narrative of Steig. I will take into account the stylistic aspects of speech, both the original English. With reference to the film adaptation, we will proceed the same way, but limited in scenes that will focus on as most important for analysis. I assume that the film version of the tale expands the rereading procedure, establishing a broader dialogue with the genre itself. I will concentrate on the nature of the Shrek character, built like an ogre, to check, among other things, the process of grotescalização by wich Steig conducts his text. I will investigate how the grotesque contributes to the rereading of the genre both in written narrative and in its film adaptation. I am, thereby, to contribute to studies of fairy tale genre and for literature studies aimed at children and young people